Faktor yang mempengaruhi Faktor yang Mempengaruhi Ketersediaan Pemberian Asi Eksklusif pada Pertumbuhan dan Perkembangan Bayi Usia 6 Bulan : Pertumbuhan dan Perkembangan Bayi Usia 6 Bulan - Leon Lau; Ernaawaty Tamba; Donna Mesina Pasaribu (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Based on data from the Ministry of Health of the Republic of Indonesia, in 2013 the coverage of exclusive breastfeeding was 54.3%, but there are still many provinces that have not reached the coverage rate of exclusive breastfeeding. According to the World Health Organization (WHO), the achievement rate is still 50%. The impact that occurs from not giving exclusive breastfeeding is the delay in growth and development of infants. The baby's growth rate is strongly influenced by the quality of breastfeeding, so it is necessary to know the factors that influence the availability of breast milk from a mother. This study aims to determine the effect of exclusive breastfeeding and other factors that can affect the growth and development of infants aged 6 months. This research was conducted on six-month-old babies, at the Grogol Petamburan Community Health Center, in the period October 2016 – September 2020 using a questionnaire. The data were then collected and processed using the SPSS application. The results showed that the coverage of exclusive breastfeeding at the Puskesmas Grogol Petamburan had reached the coverage recommended by WHO. This study concluded that there was a relationship between exclusive breastfeeding and the baby's length, weight and development.